Levels of Salt Reduction in Bread, Acceptability and Purchase Intention by Urban Mozambican Consumers - Jessen, N (2022)
Excess sodium (Na) consumption is implicated in several health problems, particularly hypertension, and bread is an important dietary source. We aimed to analyze perception of salt, acceptability, and purchase intention of low-salt and unsalted white bread by consumers in Mozambique. Sensory evaluation was performed using a triangular test (N = 42) to perceive if differences in saltiness were detected when comparing low-salt and unsalted with salt-reduced white bread. Nine-point hedonic and five-point purchase intention scales were used to measure acceptability and purchase intention, respectively (N = 120). Difference in saltiness was not detected when fresh white bread with 282 mg Na/100 g vs. 231 mg Na/100 g and 279 mg Na/100 g vs. 123 mg Na/100 g were compared. Difference in saltiness was not detected when comparing unsalted vs. 64 mg Na/100 g, while differences were detected when unsalted vs. 105 mg Na/100 g and unsalted vs. 277 mg Na/100 g were compared. Overall acceptability and purchase intention were not affected by reductions of Na in bread. A reduction of up to more than 50% of Na was not perceived and a small level of Na was not distinguished from unsalted bread. Consumers were shown to accept and be willing to buy both unsalted and salt-reduced bread, suggesting that Na can be reduced from current levels.